SURGICAL TREATMENT OF SHRAPNEL FRAGMENTED FRACTURES OF THE DISTAL END OF THE HUMERUS - Эранов Нурали Файзиевич (European Science Publishing, 2025)
The article presents operative methods of treatment of patients with fragmented fractures of the distal end of the humerus in 79 patients. The patients were divided into three groups depending on the method of surgical treatment. The results of treatment of surgical methods of all three groups were studied and conclusions were made.
Keywords: Fragmented fracture, contracture, ankylosis, osteoporosis, osteotomy.